Skema Penentuan Posisi Lingkungan Indoor untuk Aplikasi Monitoring Lokasi Dosen Berbasis Multilaterasi - Muntaqo Alfin Amanaf Mail; Dettia Wenny Brigitta; Rafina Destriarti Ainul (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Nowadays, technology is growing and helping the human work. One of those technologies is object mapping or localization in an indoor environment. The technology is often used to determine position is Global Positionig System (GPS). However, GPS signal is difficult to receive when the device is inside a room or building. Therefore, in this research Indoor Localization is implemented at Telkom Institute of Technology Purwokerto with Wireless Sensor Network (WSN) which uses ZigBee as communication protocol. One of indoor localization stages is distance estimation, which in this case, is carried out using Received Signal Strength Indicator (RSSI) by grouping the value of Path Loss Exponent (PLE) based on room characteristics (clusters). Some methods for position estimation based on number of reference nodes are trilateration and multilateration methods. From the measurement results, the distances estimation with PLE clusters has an error of 0.534 meters and PLE without clusters has an error of 0.903 meters. For accuracy estimation, the best position is obtained on PLE cluster multilateration that has the value of 0,714 meters for Mean Square Error (MSE) and 1.2 meters for the lowest value MSE at trilateration without PLE clusters. The computational time of the four methods (multilateration without PLE clusters, trilateration without PLE cluster, multilateration with PLE clusters, and a trilateration with PLE clusters) are almost identical, between 8.72 to 8.75 second.